Caregiver perspectives on the continued impact of the COVID-19 pandemic on children with intellectual/developmental disabilities - Northrup, R. A.; Jones, E.; Singh, V.; Holingue, C.; Meck, M.; Gurnett, C. A.; van Stone, M.; Kalb, L. G. (Frontiers in Pediatrics, 2023)
The COVID-19 pandemic has significantly impacted caregivers, especially those raising a child with an intellectual/developmental disability (IDD). While research has shown substantial disruption to the family, school, and occupational lives of the IDD community, little is known about the long-term impacts of COVID-19. To address this question, 249 caregivers were surveyed via an online questionnaire, between April and August of 2022 (more than 2 years into the pandemic) about potential impacts of the COVID-19 pandemic on their child's access to health-and school-based therapeutic services, caregiver mental health, and family life. The majority of caregivers reported disruptions in access to and quality of school-based therapeutic services for their child as well as a reduction in educational accommodations in the 2021-2022 academic year. Nearly half of caregivers reported feeling anxious and almost a quarter reported feeling depressed for the majority of their days. More than half of respondents reported decreased social support, and one-fifth reported employment disruptions and decreased access to food. These findings suggest that families of children with IDD are still experiencing ongoing negative impacts of the pandemic, emphasizing the critical need for continued support in the wake of the initial and more obvious disruptions caused by the COVID-19 outbreak.